Drugs : America's Holy War. - Benavie, Arthur (Taylor and Francis, 2012)
Using the best scientific evidence, Drugs: America's Holy War explores the impact and cost of America's ""War on Drugs""--Both in tax spending and in human terms. Is it possible that US drug policies are helping to proliferate, not prevent, a multitude of social ills including: homicide, property crime, the spread of AIDS, the contamination of drugs, the erosion of civil liberties, the punishment of thousands of non-violent people, the corruption of public officials, and the spending of billions of tax dollars in an attempt to prevent certain drugs from entering the countr.